Internalisasi Etika: Menjadikan Hidup, Bukan Hanya Sekedar Hidup - Megawati Naibaho; Dominikus Doni Ola; Fidelis Den (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
In our life, to choose what is good and to act rightly always required human freedom. Human freedom must be created peace and justice in order to open mind and heard for the common good for all. All people of God are witness for social justice teaching support for beautiful and meaningful life such as appreciation for the human person dignity’s, awareness of equality, equal participation, and human solidarity. This research use a qualitative method through a literature study in order to acquire data and discover the problem more profoundly. Researchers believe that the successful process of internalizing ethics aims to make life, not just a life that lasts from time to time, but a life that is organized regularly and ultimately reaches the aim of life. This research will answer the “question” is virtue ethics necessary or only an accessory for human beings’ life. Then, researchers will go further to describe the important values or practices of virtue ethics in daily life. Finally, this research proposes the practical implication based on the critical reflection and suggestion. This implication is an indication for every person to believe that the process of internalizing Ethics is an important way of life.